Safety profile of camrelizumab: An analysis based on literature and database review - Yi Huang; Wei Li (PLoS ONE, 2026)
Objective Real-world studies on the safety of camrelizumab are scarce. This study aimed to investigate the adverse drug reactions (ADRs) associated with camrelizumab and evaluate their clinical characteristics and management. Methods We retrieved data on ADRs related to the PD-1 inhibitor camrelizumab from the World Health Organization (WHO) adverse event reporting system database (VigiAccess) for the period from June,2019 to July 2025. Additionally, we conducted a retrospective analysis of case reports and case series on camrelizumab-related ADRs published from 2019 to 2025. Results 601 ADR reports were included in the VigiAccess database. Asian patients accounted for 99% (597/601), and the majority were male (69%). The most common classification of systemic organs (SOC) is hematological disorders (21.8%), skin reactions (14.3%), and systemic symptoms (8.8%). The main adverse reactions were: Hematological system: bone marrow suppression (10.3%), thrombocytopenia (5.1%); Skin: rash (5.7%), pruritus (4.3%), reactive capillary hyperplasia (RCCEP); systemic: fever (2.6%), chest pain (2.1%); serious events: myocarditis (1.2%), toxic epidermal necrolysis (TEN). Literature analysis included 80 patients (from China), with a median age of 60 years (range 20–84), and 72.5% were male. The main indications are non-small cell lung cancer (20%), nasopharyngeal carcinoma (20%) and hepatocellular carcinoma (11.3%). The median occurrence time of adverse reactions was 8 weeks (ranging from 10 minutes to 88 weeks). Typical ADRs include: cutaneous toxicity (45 cases, 56.3%); RCCEP (32 cases), Stevens-Johnson (SJS)/TEN (5 cases); hematological toxicity (38 cases, 47.5%): bone marrow suppression (22 cases), thrombocytopenia (16 cases); cardiotoxicity (13 cases, 16.25%), mainly myocarditis; Others: immune hepatitis (6 cases), thyroid dysfunction (5 cases). Conclusion The ADRs of camrelizumab are primarily hematologic and skin toxicities, with a need to be vigilant for late-onset serious events (e.g., myocarditis, TEN). Early identification and corticosteroid intervention are key management strategies.